TRANSFORMATION KEUANGAN: ANALISIS DAMPAK KEBIJAKAN SPIN OFF PADA ASURANSI ASKRIDA SYARIAH - Sanawi, Sanawi; Aini, Qurrotu; Wildandini, Azima (UIN Sultan Maulana Hasanuddin Banten, 2023)
Using data from the insurance statistics of PT Asuransi Askrida Syariah, this study will compare the conditions before and after the spin off. In accordance with the decree letter No. KEP-104/D.05/2017 circulated on December 28, 2017, the Financial Services Authority (OJK) has granted an operational license to this company. One of the sharia business units (UUS) of PT Asuransi Bangun Askrida, Askrida Syariah, officially separated itself from the Holding Company. This research will compare the performance of PT Asuransi Bangun Askrida Syariah in the period of 4 years before and 4 years after spin off using profitability. To complete this analysis, a paired sample t-test was conducted. The profitability results show that there is a difference between before and after the spin off on the financial performance of PT Askrida Syariah with the results of Return on Assets (RoA) and Return on Equity (RoE) of the company decreased after the spin off.